Comparison of Effects on Gene Expression Activity of Low-Molecular-Weight Lychee Fruit Polyphenol (Oligonol®), Adenosine, and Minoxidil in Human Dermal Papilla Cells - Koji Wakame; Akifumi Nakata; Keisuke Sato; Yoshihiro Mihara; Jun Takanari; Atuya Sato; Ken-ichi Komatsu (Faculty of Medicine, Diponegoro University, 2017)
Background: Oligonol® (OLG) is a functional food product and ingredient for cosmetics derived from a lychee fruit polyphenol. It has been reported to act on the skin as an anti-inflammatory and prevent UVB-induced skin damage.Aim: In this study, with the aim of exploring new functionalities of OLG on the scalp, we investigated the effect of OLG on human dermal papilla cells by comparing with adenosine and minoxidil at the genetic level.Method: OLG, adenosine, and minoxidil were applied to human dermal papilla cell lines for 24 h, after which VEGF, FGF-7, WNT5a, and WNT10a mRNA expressions were measured by real-time PCR analysis. Additionally, using DNA microarrays, we investigated the effect on 205 inflammation-related genes.Result: Consequently, in human dermal papilla cell lines, FGF-7 and WNT10a mRNA expression were observed in 100 µg/mL OLG-supplemented cells. The results of the DNA microarray analysis showed that 10 genes were suppressed by OLG.Conclusions: OLG may be expected to affect function of human dermal papilla cell by regulating the expression of genes related to cell proliferation and inflammation.